2013
DOI: 10.1111/jcpp.12099
|View full text |Cite
|
Sign up to set email alerts
|

The interacting effect of the BDNF Val66Met polymorphism and stressful life events on adolescent depression is not an artifact of gene–environment correlation: evidence from a longitudinal twin study

Abstract: There is a true G × E effect underlying the observed interaction between BDNF Val66Met polymorphism and environmental stress on depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 49 publications
1
23
1
3
Order By: Relevance
“…Our findings are also not in agreement with G x E studies that found an interactive effect of the higher functioning Val66 allele and environmental exposures (i.e. adversity, negative stressors, recent life events) on psychopathology, such as increased levels of neuroticism, harm avoidance and depression (Chen et al, 2013; Kim et al, 2009; Lehto et al, 2016). Apart from the possible confounding effects of age and gender, discrepant results across studies may in part be due to population-driven differences in BDNF Val66Met frequencies, given that the Met66 allele has consistently been found to be more common in Asian populations than in Caucasian populations (Chen et al, 2013; Petryshen et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings are also not in agreement with G x E studies that found an interactive effect of the higher functioning Val66 allele and environmental exposures (i.e. adversity, negative stressors, recent life events) on psychopathology, such as increased levels of neuroticism, harm avoidance and depression (Chen et al, 2013; Kim et al, 2009; Lehto et al, 2016). Apart from the possible confounding effects of age and gender, discrepant results across studies may in part be due to population-driven differences in BDNF Val66Met frequencies, given that the Met66 allele has consistently been found to be more common in Asian populations than in Caucasian populations (Chen et al, 2013; Petryshen et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings suggest that the BDNF Val66Met polymorphism does not have a direct effect on AS. This finding is in line with studies that have found no significant direct association between BDNF Val66Met polymorphism and personality traits such as neuroticism or harm avoidance and anxiety disorders or mood disorders, including OCD, panic disorder, PTSD and depression (Arias et al, 2012; Chen et al, 2013; Frustaci et al, 2008; Hong et al, 2012; Minelli et al, 2011; Surtees et al, 2007; Terracciano et al, 2010), despite some studies reporting such associations (Frustaci et al, 2008; Lang et al, 2005; Min et al, 2013; Montag et al, 2010; Sen et al, 2003; Terracciano et al, 2010). Firstly, the grouping of Met66 allele carriers (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nobile et al, 2008;Campbell et al, 2013;Chen, Li, & McGue, 2013;Cents et al, 2014). Some considerations on which JCPP's decisions whether to accept or reject reports of trait/disorder-gene association may guide authors when planning their studies; however, under certain circumstances other types of studies might add value and may be acceptable too.…”
mentioning
confidence: 99%